Improving the processability and cycling stability of nano-LiFePO4 cathode by using PVDF/TX binary binder. Issue 11 (2nd November 2019) - Liu, Shuling; Zhong, Haoxiang; Zhang, Congcong; Yan, Xiaodan; Zhao, Xinyue; Zhang, Lingzhi
ABSTRACT: In lithium-ion battery industry, the nanoscale electrode materials usually have difficulty to be dispersed well in the electrode slurry. The inferior processability thus results in deteriorated electrochemical performances of the cell. In this work, poly(vinylidene fluoride) (PVDF) and terpene resin (TX) as a binary binder are used to improve the dispersibility and cycling stability of nanoscale LiFePO4 (nano-LFP) cathode. The wettability, dispersibility, adhesion strength and electrochemical performance of nano-LFP cathode using PVDF/TX are measured and compared with that using only PVDF binder. Nano-LFP cathode using PVDF/TX binder (the optimal ratio of PVDF to TX is 97:3) exhibits better dispersibility and stronger adhesion strength than that of PVDF. In addition, nano-LFP cathode with PVDF/TX binder shows better cycling stability, rate capability, and electrochemical kinetics than that with PVDF, retaining 97.4% capacity after 100 cycles test at C/5 in room temperature and 93.4% capacity after 60 cycles test at C/2 in 55℃, respectively. GRAPHICAL ABSTRACT: